Technologies in digital literacy training: how are collaborative, seamless, and online learning approaches utilized? - Trilisiana, Novi; Surjono, Herman Dwi; Rukiyati, Rukiyati; Wahyuningsih, Dian (Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
Digital literacy has become an essential competency for educators in the context of rapidly evolving educational technologies and the increased prevalence of online and blended learning environments. However, the effective integration of collaborative and seamless learning approaches into digital literacy training remains a significant challenge, particularly due to disparities in technology access and varying pedagogical practices. This systematic study examines the utilization of technology in digital literacy training for instructors, emphasizing collaborative learning, seamless learning, and online learning methodologies. Out of an initial review of 95 articles from the Education Resources Information Center (ERIC), 15 were chosen based on relevancy and inclusion criteria. The investigation indicates that Learning Management Systems like Moodle, Google Classroom, and Blackboard are frequently utilized for the administration of digital content, assignments, and evaluations. Moreover, collaboration platforms such as Google Docs, Zoom, and Microsoft Teams enhance group discussions and projects. The digital literacy curriculum encompasses a spectrum of skills, from fundamental to advanced, including the utilization of instructional tools, management of digital content, digital security, and proficiency in social media. Mobile gadgets in Bring Your Own Device (BYOD) models facilitate uninterrupted, adaptable learning. Notwithstanding the benefits, access to gadgets and internet connectivity continues to pose a considerable barrier. This study shows that customized digital literacy curriculum can improve educators' skills, however further support is necessary to overcome technological obstacles. Further research is recommended to explore scalable solutions that can bridge these gaps and promote equitable digital literacy training across diverse educational contexts.